The Republic of Latvia : Poverty Assessment, Volume 2 - World Bank (Washington, DC, 2013)
This poverty assessment, focuses on three areas. The first is an update of the poverty profile, who are the poor in Latvia in 1998 and what determines their low level of income. The second looks at the labor market: determinants of earnings, and unemployment. The third assesses how the system of social assistance functions, including: who are the recipients of social assistance, what is the amount of "leakage", and why are certain households excluded. The functioning of social assistance is also linked with the issue of regional inequality in its delivery - a problem that has been repeatedly highlighted in the Latvian context.